En analys av regeringens utredning om carried interest - Björkquist Saldert,John (2025)
Carried interest has been debated in tax law for most of the 2000s. This concept, which forms part of the fees allocated to a private equity firm for managing a private equity fund, results in asymmetric returns for certain key individuals. The question of how this compensation should be taxed for the recipient has been debated and, at the time of writing, remains a current issue. In the Swedish income tax system, there are no specific rules addressing carried interest, unlike in several other countries where such regulations have been implemented. In 2024, the Swedish government initiated an inquiry aimed at examining how this type of income could be taxed in a way that corresponds to the taxation of closely held business owners. The purpose of this paper is to investigate how carried interest arises and how it has historically been handled by courts and stakeholders. The inquiry confirms that carried interest is a well-established model for determining compensation for fund managers. The model allows key individuals within the private equity sphere, in various ways, to invest in the fund. If the fund yields a return above a certain predetermined threshold, these individuals receive a return that exceeds their initial investment. Regarding the historical processes, the paper finds that the debate has centered partly on whether the income can be considered as remuneration for work, and therefore taxed as earned income, and partly on how the various requirements in the closely held company rules should be applied to the situation. Furthermore, the paper aims to analyse the legislative proposal presented in the inquiry, using findings from previous chapters. The inquiry is particularly analysed considering the fundamental principles of the income tax system. Among the conclusions drawn, it is clear that the proposed legislation could contribute to greater predictability for the involved stakeholders. However, in some respects, criticism may be directed at the fact that the taxation does not fully "correspond" to the taxation of closely held companies. For many individuals receiving carried interest, the proposal—if enacted into law— would mean a less favourable tax treatment. Nevertheless, the inquiry has been welcomed by several actors such as the Swedish Private Equity & Venture Capital Association (SVCA) and the Swedish Tax Agency, indicating a general desire to establish a predictable framework for fund managers.
Keywords: Skatterätt